ANALISIS PENILAIAN KOMPOTENSI SIKAP SISWA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI KELAS XI SMK NEGERI 1 ARAMOTAHUN PEMBELAJARAN 2020/2021 - Apilianus Duha; Sesuaikan Sarumaha; Maria Magdalena Duha (Universitas Nias Raya, 2022)
This research is based on the results of interviews conducted by researchers at SMK Negeri 1 Aramo, reseachhers found that the learning success of students in atitude competence can be categorized as low. This is due to the fact that the learning carried out in the classroom only focuses on the areas of students’ abilices and atitudes. This study aims to find out how the studens’ atitude competence assessment in ovies learning in class XI SMK Negeri 1 Aramo and to fint out how the atitude competence of students in learning civies in class XI SMK Negeri 1 Aramo. To addres these problems, the researchers conducted research on the analysis of studens affitude competency assossment in learning pancasila and otizenship eeducation in class XI of SMK Negeri 1 Aramo for the 2020/2021 academic year, the apor approach used in this research is a qualitative approach and the type of clasoitive research. Sources of data in this study consisted of seacher of Pancasila and zitizenship education, and 5 studens, the data cefection technique used is though the stages of clasevation, interviews and clocumentation. Data analysis was caried out though there activity ines (1) data reduction, (2) data presentation , and (3) crawing conclusions. Based on the resuts of research conducted by researchers that. Civics educations teachers at SMK Negeri 1 Aramo have carried out a good student aftitude competency assessment in learning Pancasila and citizensship educations, the researcher suggets that Pancasila and citizenship educations teachers should provide an assessement of student atitude competence luring the implementation of learning in the classroom. Pancasila education and zitizenship teachers should routinely foster, motivate and direct studens in the formation of good atitudes and charcter and be able to become studens who are devoted to god alrnighty. Pancasila and zitizenship educations teachers should continue to use curriculum 13 at the same time, implementation of learning in the classroom, as well as Pancasila and civic educations teaachers should foster studen atitudes so that they become devoted to god alrrighty.